Analysis of Health Promotion and Cancer Prevention Within the CanCon JA Project - Arnič, Maja; Bračko, Brina; Marjetka Jelenc, Marjetka Jelenc (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The European Union, which is the cradle of the promotion and preventive and national programs for cancer control, as a continuously developing community, has introduced a number of projects and programs for performance control, the production of key documents intended for political decision-makers in the formulation of measures in the field of comprehensive treatment of cancer. The document offers possibilities for improving the acquisition of financial resources for disease control. The fields of preventive and promotional cancer are based on the good compliance of society and have a lot of room for improvement in the time of rapid technological progress. The current state and past efforts in the field of cancer prevalence can be seen in the research called European Guide on Quality Improvement in Comprehensive Cancer Control - CanCon JA, and the research also offers a comparison in the field of prevention and promotion between many European countries. The aim of the paper is to compare the promotion and prevention of the Slovenian national program for cancer control with the programs of the countries with a long tradition and to analyze the results.